HUD liquid crystal display module capable of improving antistatic capability
By pasting conductive double-sided adhesive on the exposed position of the shielding layer of the HUD liquid crystal display module, it directly conducts with the surface iron frame, solving the problem of excessively long electrostatic release path in the prior art, and significantly improving the anti-static ability.
Patent Information
- Application Number
- CN202421017013.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2034-05-11
AI Technical Summary
The electrostatic release path of existing HUD liquid crystal display modules is long, resulting in limited antistatic ability.
By pasting conductive double-sided adhesive in the exposed position of the shielding layer, it is directly connected to the surface iron frame to shorten the electrostatic release path.
A larger on-circuit area and lower resistance are achieved, significantly improving the anti-static ability of the HUD display module.
Smart Images

Figure CN222618910U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of liquid crystal display modules, in particular to a HUD liquid crystal display module with improved anti-static capability. Background Art
[0002] A liquid crystal display module is an electronic component used to display images and text. It consists of one or more liquid crystal screens and can display text, images and other information.
[0003] Conventional HUD modules use silver paste to release static electricity received by the screen surface. Figure 7 , Figure 8 as well as Fig. 9 As shown in the figure, the TFT display screen is mainly composed of a surface polarizer, an upper TFT glass, a lower TFT glass and a bottom polarizer. A shielding layer is set on the surface of the upper TFT glass, and the shielding layer is made of ITO. When the screen surface receives static electricity, the static electricity will be conducted to the lower TFT glass through the silver paste on the shielding layer, and then transmitted to the FPC through the metal traces on the lower TFT glass, and then released to the client's case and other devices through the grounding points such as the FPC reinforcement.
[0004] Through research on existing technologies, we found that the above method will result in a longer electrostatic release path. In addition, due to the limited size of the silver paste dots and the thin TFT and FPC traces, the resistance of the entire path will be relatively large and the anti-static ability will be limited.
[0005] Therefore, in view of the defects of the existing technology, we designed a HUD liquid crystal display module that replaces silver paste with conductive double-sided tape to improve its anti-static ability. Utility Model Content
[0006] The utility model aims to overcome the above-mentioned shortcomings and provide a technical solution that can solve the above-mentioned problems.
[0007] To achieve the above-mentioned purpose, the utility model provides the following technical solutions: a HUD liquid crystal display module with improved antistatic ability, comprising a front iron frame and a rear iron frame, wherein a lower TFT glass, an upper TFT glass, a bottom polarizer, a shielding layer and a front polarizer are arranged between the front iron frame and the rear iron frame; the lower TFT glass is connected to the upper TFT glass, and one side of the bottom polarizer is connected to the lower TFT glass; the shielding layer is connected to one side of the upper TFT glass, and the front polarizer is arranged on one side of the shielding layer, and the top and bottom of one side of the shielding layer are both bonded with conductive double-sided tape, and the inner side of the front iron frame is bonded to the conductive double-sided tape.
[0008] As a further solution of the utility model: the two conductive double-sided adhesive tapes are centrally arranged at the top and bottom of one side of the upper TFT glass, and the lengths of the two conductive double-sided adhesive tapes are shorter than the length of the upper TFT glass.
[0009] As a further solution of the utility model: the gap between the shielding layer and the surface iron frame is 0.4 mm, and the thickness of the two conductive double-sided adhesive tapes is 0.4 mm.
[0010] As a further solution of the utility model: the distance between the top edge of the surface polarizer and the top edge of the upper TFT glass, and the distance between the bottom edge of the surface polarizer and the bottom edge of the upper TFT glass are both equal to the width of the conductive double-sided tape.
[0011] As a further solution of the utility model: a window is provided on the front side of the surface iron frame, and a TFT display area is provided in the window of the surface iron frame.
[0012] As a further solution of the utility model: the length of the upper TFT glass is the same as that of the lower TFT glass, the top edge of the upper TFT glass and the top edge of the lower TFT glass are on the same horizontal line, and the width of the upper TFT glass is smaller than that of the lower TFT glass.
[0013] As a further solution of the utility model: a binding area is left between the bottom edge of the upper TFT glass and the bottom edge of the lower TFT glass.
[0014] As a further solution of the utility model: an FPC body is mounted and bound on the binding area of the lower TFT glass, the FPC body passes through the bottom of the surface iron frame and the rear iron frame, and a stainless steel reinforcement is also provided on the bottom of one side of the FPC body.
[0015] As a further solution of the utility model: a driver IC is also mounted and bound on the binding area of the lower TFT glass and at a position far away from the FPC body.
[0016] As a further solution of the utility model: the inner side of the rear iron frame is bonded to the bottom polarizer through single-sided sticky foam and is buckled together with the surface iron frame.
[0017] Compared with the prior art, the beneficial effects of the utility model are as follows:
[0018] In the present application, the shielding layer is exposed by reducing the size of the upper and lower sides of the polarizer, and a conductive double-sided tape of corresponding size is affixed to the exposed position. Through the above adjustment, there is no need to apply silver paste, and the ITO of the shielding layer can be directly connected to the surface iron frame. This conduction area is large, the resistance is low, and the path is extremely short. When the surface of the LCD screen receives static electricity, it can be quickly released to the surface iron frame through the conductive double-sided tape, and then quickly released to the customer's case and other equipment, thereby greatly enhancing the anti-static ability of the HUD display module. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the side sectional structure of the utility model as a whole;
[0020] Figure 2 This utility model Figure 1 A is an enlarged structural diagram;
[0021] Figure 3 It is a front view structural schematic diagram of the utility model;
[0022] Figure 4 It is a front cross-sectional structural schematic diagram of the utility model;
[0023] Figure 5 It is a side sectional structural schematic diagram of the utility model when the front iron frame and the rear iron frame are not buckled together;
[0024] Figure 6 This utility model Figure 5 The enlarged structural diagram at B in FIG.
[0025] Figure 7 It is a front view structural diagram of a conventional design scheme of the prior art;
[0026] Figure 8 It is a side cross-sectional structural schematic diagram of a conventional design scheme in the prior art;
[0027] Fig. 9 It is a schematic diagram of the electrostatic discharge path of the conventional design scheme of the existing technology.
[0028] The reference numerals and names in the figures are as follows:
[0029] 1. Front iron frame; 101. Window; 102. TFT display area; 2. Rear iron frame; 3. Lower TFT glass; 4. Upper TFT glass; 5. Bottom polarizer; 6. Single-sided sticky foam; 7. Shielding layer; 8. Front polarizer; 9. Conductive double-sided tape; 10. Driver IC; 11. FPC body; 12. Stainless steel reinforcement. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0031] See also Figure 1-6 A HUD liquid crystal display module with improved antistatic ability includes a front iron frame 1 and a rear iron frame 2, a window 101 is opened on the front of the front iron frame 1, and a TFT display area 102 is set in the window 101 of the front iron frame 1, and a lower TFT glass 3, an upper TFT glass 4, a bottom polarizer 5, a shielding layer 7 and a surface polarizer 8 are arranged between the front iron frame 1 and the rear iron frame 2; the lower TFT glass 3 is connected to the upper TFT glass 4, and one side of the bottom polarizer 5 is connected to the lower TFT glass 3; the shielding layer 7 is connected to one side of the upper TFT glass 4, and the surface polarizer 8 is arranged on one side of the shielding layer 7, and the top and bottom of one side of the shielding layer 7 are both bonded with conductive double-sided adhesive 9, the inner side of the front iron frame 1 is bonded with the conductive double-sided adhesive 9, and the inner side of the rear iron frame 2 is bonded to the bottom polarizer 5 through a single-sided adhesive foam 6 and is buckled with the front iron frame 1.
[0032] Specifically, the present application reduces the size of the upper and lower sides of the surface polarizer 8 to expose the shielding layer 7, and affixes a conductive double-sided tape 9 of a corresponding size to the exposed position. Unlike the conventional design module that first fixes the LCD screen to the rear iron frame 2, the present application changes it to a method in which the LCD screen is first glued and fixed to the surface iron frame 1 by the conductive double-sided tape 9, and then the rear iron frame 2 is buckled.
[0033] See also Figure 4 In this embodiment, two conductive double-sided adhesive tapes 9 are centrally arranged at the top and bottom of one side of the upper TFT glass 4 , and the lengths of the two conductive double-sided adhesive tapes 9 are shorter than the length of the upper TFT glass 4 .
[0034] Specifically, the length of the conductive double-sided adhesive 9 is more than 0.5 mm shorter than one side of the upper TFT glass 4 , which can better avoid the conductive double-sided adhesive 9 from exceeding the two sides of the upper TFT glass 4 when being affixed, and ensure the regularity of the conductive double-sided adhesive 9 .
[0035] See also Figure 1-2 In this embodiment, the gap between the shielding layer 7 and the surface iron frame 1 is 0.4 mm, and the thickness of the two conductive double-sided adhesives 9 is 0.4 mm.
[0036] Specifically, the thickness of the conductive double-sided tape 9 is the same as the gap between the shielding layer 7 and the surface iron frame 1. The shielding layer 7 and the surface iron frame 1 can be bonded to each other using the two sides of the conductive double-sided tape 9, so that the ITO of the shielding layer 7 can be directly connected to the surface iron frame 1.
[0037] See also Figure 4-6 In this embodiment, the distance between the top edge of the plane polarizer 8 and the top edge of the upper TFT glass 4 and the distance between the bottom edge of the plane polarizer 8 and the bottom edge of the upper TFT glass 4 are both equal to the width of the conductive double-sided tape 9.
[0038] Specifically, the size of the surface polarizer 8 is smaller than the size of the upper TFT glass 4 and the shielding layer 7 (the shielding layer 7 is attached to the upper TFT glass 4), so that the top of the shielding layer 7 can be exposed, and the conductive double-sided tape 9 can be accurately pasted on the exposed part, which has the same width as the conductive double-sided tape 9. On the one hand, it can improve the regularity after pasting and avoid overflowing glue. On the other hand, it can have a large enough conductive area to obtain lower resistance.
[0039] See also Figure 1-4 In this embodiment, the length of the upper TFT glass 4 is the same as that of the lower TFT glass 3, and the top edge of the upper TFT glass 4 is on the same horizontal line as that of the lower TFT glass 3, and the width of the upper TFT glass 4 is smaller than that of the lower TFT glass 3; a binding area is left between the bottom edge of the upper TFT glass 4 and the bottom edge of the lower TFT glass 3; an FPC body 11 is mounted and bound on the binding area of the lower TFT glass 3, and the FPC body 11 passes through the bottom of the face iron frame 1 and the rear iron frame 2, and a stainless steel reinforcement 12 is also provided at the bottom of one side of the FPC body 11; a driver IC 10 is also mounted and bound on the binding area of the lower TFT glass 3 and at a position away from the FPC body 11.
[0040] Specifically, the length of the upper TFT glass 4 is the same as that of the lower TFT glass 3, which facilitates the bonding of the two to achieve three parallel sides and facilitates subsequent use. The width of the upper TFT glass 4 is smaller than that of the lower TFT glass 3, which is convenient for reserving a binding area, so that the FPC body 11 and the driver IC 10 can be bound in the binding area, thereby facilitating subsequent assembly and ensuring stable operation.
[0041] The utility model is implemented by the following scheme:
[0042] By reducing the size of the upper and lower sides of the surface polarizer 8, the shielding layer 7 is exposed, and a conductive double-sided tape 9 of corresponding size is affixed to the exposed position. Unlike the conventional design module that first fixes the LCD screen to the rear iron frame 2, the utility model changes the LCD screen to be first pasted and fixed to the surface iron frame 1 by the conductive double-sided tape 9, and then the rear iron frame 2 is buckled, and the double-sided tape foam on the rear iron frame 2 is designed to be a single-sided sticky foam 6 of the same size and thickness, so as to avoid the problem of internal stress pulling each other due to the double-sided tape on the front and back of the LCD screen after assembling the rear iron frame 2. At the same time, the single-sided sticky foam 6 can play a supporting role to avoid the problem of the LCD screen falling easily.
[0043] In order to ensure that the surface polarizer 8 has enough area to cover the upper TFT glass 4, the distance between the side of the surface polarizer 8 and the AA area is designed to be more than 1.0 mm. In order to ensure the feasibility of cutting and convenient pasting of the conductive double-sided adhesive 9, and to have a sufficiently large conductive area to obtain lower resistance, the width of the conductive double-sided adhesive 9 is designed to be more than 1.0 mm. In addition, the thickness of the selected conductive double-sided adhesive 9 is equal to the gap between the shielding layer 7 and the surface iron frame 1 (as shown in the attached figure). Figure 1-2 As shown in the figure, the gap between the shielding layer 7 and the surface iron frame 1 is 0.4mm, so the thickness of the conductive double-sided adhesive tape 9 is also selected to be 0.4mm. At the same time, in order to prevent the conductive double-sided adhesive tape 9 from exceeding the upper TFT glass 4 when being attached, the length of the conductive double-sided adhesive tape 9 is designed to be more than 0.5mm smaller than the single side of the upper TFT glass 4 (as shown in the figure). Figure 4 shown).
[0044] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention. Any reference numeral in a claim should not be regarded as limiting the claim to which it relates.
Claims
1. A HUD liquid crystal display module with improved antistatic capability, characterized in that: It comprises a front iron frame (1) and a rear iron frame (2), wherein a lower layer of TFT glass (3), an upper layer of TFT glass (4), a bottom polarizer (5), a shielding layer (7) and a front polarizer (8) are arranged between the front iron frame (1) and the rear iron frame (2); The lower TFT glass (3) is connected to the upper TFT glass (4), and one side of the bottom polarizer (5) is connected to the lower TFT glass (3); The shielding layer (7) is connected to one side of the upper TFT glass (4), the surface polarizer (8) is arranged on one side of the shielding layer (7), the top and bottom of one side of the shielding layer (7) are both bonded with conductive double-sided adhesive (9), and the inner side of the surface iron frame (1) is bonded to the conductive double-sided adhesive (9).
2. The HUD liquid crystal display module with improved antistatic capability according to claim 1, characterized in that: The two conductive double-sided adhesive tapes (9) are both centrally arranged at the top and bottom of one side of the upper TFT glass (4), and the lengths of the two conductive double-sided adhesive tapes (9) are both shorter than the length of the upper TFT glass (4).
3. The HUD liquid crystal display module with improved antistatic capability according to claim 1, characterized in that: The gap between the shielding layer (7) and the surface iron frame (1) is 0.4 mm, and the thickness of the two conductive double-sided adhesive tapes (9) is 0.4 mm.
4. The HUD liquid crystal display module with improved antistatic capability according to claim 1, characterized in that: The distance between the top edge of the planar polarizer (8) and the top edge of the upper TFT glass (4), and the distance between the bottom edge of the planar polarizer (8) and the bottom edge of the upper TFT glass (4) are both equal to the width of the conductive double-sided adhesive (9).
5. The HUD liquid crystal display module with improved antistatic capability according to claim 1, characterized in that: A window (101) is provided on the front side of the surface iron frame (1), and a TFT display area (102) is provided in the window (101) of the surface iron frame (1).
6. The HUD liquid crystal display module with improved antistatic capability according to claim 1, characterized in that: The length of the upper TFT glass (4) is the same as that of the lower TFT glass (3), the top edge of the upper TFT glass (4) and the top edge of the lower TFT glass (3) are on the same horizontal line, and the width of the upper TFT glass (4) is smaller than that of the lower TFT glass (3).
7. The HUD liquid crystal display module with improved antistatic capability according to claim 6, characterized in that: A binding area is left between the bottom edge of the upper TFT glass (4) and the bottom edge of the lower TFT glass (3).
8. The HUD liquid crystal display module with improved antistatic capability according to claim 7, characterized in that: An FPC body (11) is mounted and bound on the binding area of the lower TFT glass (3); the FPC body (11) passes through the bottom of the front iron frame (1) and the rear iron frame (2); and a stainless steel reinforcement (12) is also provided at the bottom of one side of the FPC body (11).
9. The HUD liquid crystal display module with improved antistatic capability according to claim 7, characterized in that: A driver IC (10) is also mounted and bound on the binding area of the lower TFT glass (3) and at a position away from the FPC body (11).
10. The HUD liquid crystal display module with improved antistatic capability according to claim 1, characterized in that: The inner side of the rear iron frame (2) is bonded to the bottom polarizer (5) through a single-sided adhesive foam (6) and is buckled together with the surface iron frame (1).